KAMPUNG KARANGKAJEN YOGYAKARTA - S a ti v a S a ti v a (Inersia : Jurnal Teknik Sipil dan Arsitektur, 2005)
ABSTRACTKampong Karangkajen Yogyakarta is an old kampong that most nativeresidences are batik enterpreneur. Most of them still have close relationship,evenmore family relationship. So that there is a unique relationship among theresidences, especially in their informal relation.The aim of this research is to look for characteristic of informal gatheringspace at Kampong Karangkajen Yogyakarta, and to get determine factor of thecharacteristic, through typology study.This research uses rasionalistic-qualitative paradigm. Before analyzingthe data, the researcher studied several references, especially about typologyin architecture. The study results theory frame that will drive data analyze, thatis 9 cases of informal gathering space at Kampong Karangkajen Yogyakarta.The result of this research show that there is a typology of informal gatheringspace at Kampong Karangkajen Yogyakarta, especially in physical factor thatsupport activity comfortness. The determine factors influenced the typologyare: the users, the activities and the time when the activities happened.Keywords: typology, informal gathering space, Kampong KarangkajenYogyakarta